Clear-cell variant of oral squamous cell carcinoma: A rare entity - Ramani, Pratibha (J Oral Maxillofac Pathol, 2021)
Clear-cell variant of oral squamous cell carcinoma is an extremely rare entity in the maxillofacial region. We report a case of 42-year-old female who presented with a soft-tissue growth with erythematous and nonscrapable irregular white patches on the left alveolar mucosa for the past 3 months. Histopathologic examination showed lobules and sheets of clear cells with features of malignancy extending from the surface epithelium. Periodic acid–Schiff and mucicarmine stains showed a negative reaction. Immunohistochemical study using antibody for pan-cytokeratin revealed intense positivity and negative for the markers such as S-100, smooth muscle actin and CD 117.